Extraction of carbon powder from pyrolysis of low-density polyethylene plastics and its application in composite laminates - Kadambari C S Vyasa Krishnaji; Veeresh Kumar GB; Santosh Kumar Sahu; Mohammed Aman (MethodsX)
The escalating environmental concerns associated with plastic waste, particularly Low-Density Polyethylene (LDPE), have spurred research into sustainable recycling strategies. Pyrolysis has been developed as a viable technique for transforming LDPE into appreciated by-products, including carbon powder, which holds potential for advanced material applications. This study investigates the extraction of carbon powder from LDPE via pyrolysis and its subsequent utilization in composite laminates. • Araldite LY 556 and Aradur HY 951 epoxy resins are used to create the laminates, and carbon and kevlar fiber reinforcement are added in different weight fractions of 0 to 30 % in the intervals of 10 % of carbon char generated from LDPE. • Tensile strength (ASTM D638), flexural strength (ASTM D790), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FT-IR) and scanning electron microscopy (SEM) are used to do a thorough assessment of mechanical and structural features. • Incorporation of LDPE-derived carbon char significantly enhanced mechanical properties of epoxy-based laminates. At 30 wt % char, tensile strength increased by 75 % in carbon and 129 % in Kevlar composites, while flexural strength improved by 94 % and 196 %, respectively. SEM, XRD, and FTIR analyses confirmed improved interfacial adhesion, structural integrity, and filler stability, demonstrating char’s effectiveness as a sustainable reinforcement.